Preparation and Degradation Behavior of Composite Bio-Coating on ZK60 Magnesium Alloy Using Combined Micro-Arc Oxidation and Electrophoresis Deposition - Wang, Ze-Xin; Xu, Lei; Zhang, Jin-Wei; Ye, Fei; Lv, Wei-Gang; Xu, Cheng; Lu, Sheng; Yang, Jun (Frontiers in Materials, 2020)
In this work, ZK60 magnesium alloy was employed as the substrate for producing micro-arc oxidation (MAO) coating containing Ca and P. Electrophoretic deposition (ED) process was conducted on the micro-arc oxidized sample to prepare a hydroxyapatite (HA) layer on the original coating. X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS) and Fourier transform infrared spectroscopy (FT-IR) were used to analyze the phase constituents and microstructures of both MAO and MAO-ED coatings. Corrosion resistance and degradation behavior of the coatings in SBF were investigated by electrochemical tests and simulated body fluid (SBF) immersion tests. The results indicate that a dense HA layer about 5μm in thickness has been successfully prepared on the MAO coating. The porosity of the MAO-ED coating decreases from 5.63% before ED process to 0.81%. The Ca/P ratio of the MAO-ED coating is 1.60, indicating a potential biocompatibility. The MAO-ED coating can induce the deposition of bioactive products from SBF. During 10-day SBF immersion test, the weight gain of MAO-ED sample keeps increasing, indicating that the deposition rate of the induced products is always higher than that of corrosion products before the 10 days of immersion. The deposition of induced products effectively protects the substrate from being corroded so that it ensures the good mechanical properties and biocompatibility during the initial stage of implantation. According to the changes in sample morphologies and the electrochemical measurements in SBF, a relevant degradation model has been suggested and the underlying mechanism for degradation behavior is discussed.